Flexural Performance of FRP-Reinforced Concrete Beams Using Ultra High Strength Concrete - Mahaini, Zin Subhi (2022)
A Master of Science thesis in Civil Engineering by Zin Subhi Mahaini entitled, “Flexural Performance of FRP-Reinforced Concrete Beams Using Ultra High Strength Concrete”, submitted in April 2022. Thesis advisor is Dr. Farid Abed. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).